Effectiveness of Learning Using a Moodle – Based Learning Management System (LMS) in Improving Students’ Civic Knowledge on Diversity Materials - Rany Safitri; Sapriya Sapriya; Dadang Sundawa (Jurnal Civicus, 2023)
This research was motivated by distance learning as a result of the Covid-19 pandemic which caused the use of Moodle e-learning media in learning activities. This study uses a mixed method. Data collection techniques used are observation, interviews, cognitive tests, and questionnaires. The findings in this study; 1) Moodle-based e-learning plans for both schools and Citizenship Education teachers have developed and designed learning steps in a systematic manner that are in line with the learning objectives. 2) Based on the researcher’s observations from the opening activities, education has prepared learning resources in accordance with the lesson plans before learning begins. 3) Student learning outcomes based on cognitive tests at the end pf the lesson showed that most of the students had completed the learning sub unit with a percentage 64% of the overall class VII students which was a sample of 78 people, this was certainly influenced by the learning process in class and various assignments that have been completed by students. 4) The effectiveness of Moodle based e-learning at SMPN 30 Bandung in improving the civic knowledge of students in civics subjects, there are several things that must be considered. So it can be concluded that the use of Moodle in learning is effectively used in increasing the civic knowledge of students.